Controlled Synthesis of Hierarchically Assembled Porous ZnO Microspheres with Enhanced Gas-Sensing Properties. (19th October 2015) - You, Shengsheng; Song, Haojie; Qian, Jing; Sun, Ya-li; Jia, Xiao-hua
Abstract : The ZnO microspheres constructed by porous nanosheets were successfully synthesized by calcinating zinc hydroxide carbonate (ZHC) microspheres obtained by a sample hydrothermal method. The samples were characterized in detail with scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and thermogravimetric and differential scanning calorimetry (TG-DSC). The results indicated that the prepared ZnO microspheres were well crystalline with wurtzite hexagonal phase. The effects of reaction time, temperature, the amount of trisodium citrate, and urea on the morphology of ZnO microspheres were studied. The formation mechanism of porous ZnO microspheres was discussed. Furthermore, the gas-sensing properties for detection of organic gas of the prepared porous ZnO microspheres were investigated. The results indicated that the prepared porous ZnO microspheres exhibited high gas-sensing properties for detection of ethanol gas.